A reliable and valid assessment of upper limb movement quality after stroke: the observational Drinking Task Assessment - Minnu Jose; Maria Munoz-Novoa; Margit Alt Murphy (Medical Journals Sweden, 2024)
Objective: To develop and evaluate the reliability and validity of a new observational Drinking Task Assessment (DTA) designed to assess quality of movement in task performance after stroke. Design: Reliability and validity. Methods: The DTA measures movement time and movement quality (smoothness, trunk, shoulder, elbow, and grasp movements) on a 4-level ordinal scale. Thirty participants with chronic stroke were assessed independently by 2 therapists. Intra-class correlation (ICC), standard error of measurement (SEM) and minimal real difference (MRD), weighted kappa, percentage of agreement, and Svensson method were used for reliability assessment. Motion capture-based kinematics and established clinical scales were used to evaluate validity. Results: The absolute SEM and MRD for movement time were 0.4 and 1 s (11%), respectively. The ICC (≥ 0.93) and weighted kappa (0.71-1.0) showed good to excellent agreement for intra- and inter-rater reliability. DTA showed strong correlations with Fugl-Meyer Assessment (0.74), Action Research Arm Test (0.93), and kinematic measures of smoothness (0.93), trunk displacement (0.91), elbow extension (0.73), and shoulder movements (0.56), indicating good construct validity. Conclusions: The new DTA proved to be a reliable and valid tool for assessment of movement quality during task performance after stroke.